Seasonal dynamics of meroplankton in a sub-Antarctic fjord (Southern Patagonia, Chile) - Pineda-Metz, Santiago E. A.; Montiel San Martin, Americo Manuel (My University, 2021)
Knowledge of seasonal dynamics and composition of meroplankton (larvae of benthic invertebrates) is rather limited for sub-Antarctic regions. We studied the seasonal dynamics of meroplankton in a sub-Antarctic proglacial basin (Gallegos Sound, Chile), by examining changes in the meroplankton community in relation to hydrographic variables along four sampling cruises between early winter 2010 and late winter 2011. The local meroplankton community was composed of 39 larval morphotypes distributed among 11 major taxa, being polychaetes the best represented (15 larvae morphotypes), and bivalve the most abundant. We found distinct seasonal differences in terms of meroplanktonic composition and abundance, with higher abundance and larval morphotype number during austral spring and late winter, and lower in summer and early winter. The pattern observed for meroplankton was directly related to seasonal variations of fluorescence of chlorophyll a and temperature. We found meroplankton abundances lower than those of other sub- and Polar environments. However, meroplanktonic temporal dynamics showed a common pattern for sub- and Polar fjords, suggesting a strong link between benthic spawning and the occurrence of phytoplankton blooms.
Keywords: benthic invertebrate larvae; magellan strait; proglacial fjord; glacio-marine fjord; sub-polar; zooplankton